Characteristic functions in the Cheyette Interest Rate Model - Ingo Beyna; Uwe Wystup (Frankfurt School of Finance & Management, Centre for Practical Quantitative Finance (CPQF), 2011)
We investigate the characteristic functions of multi-factor Cheyette Models and the application to the valuation of interest rate derivatives. The model dynamic can be classiffied as an affine-diffusion process implying an exponential structure of the characteristic function. The characteristic function is determined by a model specific system of ODEs, that can be solved explicitly for arbitrary Cheyette Models. The necessary transform inversion turns out to be numerically stable as a singularity can be removed. Thus the pricing methodology is reliable and we use it for the calibration of multi-factor Cheyette Models to caps.
Keywords: 330; Cheyette Model; Characteristic Function; Fourier Transform; Calibration of Multi-Factor Models